Defining hip pain trajectories in early symptomatic hip osteoarthritis – 5 year results from a nationwide prospective cohort study (CHECK). Issue 5 (May 2016) - Bastick, A.N.; Verkleij, S.P.J.; Damen, J.; Wesseling, J.; Hilberdink, W.K.H.A.; Bindels, P.J.E.; Bierma-Zeinstra, S.M.A.
Summary: Objective: To define distinct hip pain trajectories in individuals with early symptomatic hip osteoarthritis (OA) and to determine risk factors for these pain trajectories. Method: Data were obtained from the nationwide prospective Cohort Hip and Cohort Knee (CHECK) study. Participants with hip pain or stiffness and a completed 5-year follow-up were included. Baseline demographic, anamnestic, physical examination characteristics were assessed. Outcome was annually assessed by the Numeric Rating Scale (NRS) for pain. Pain trajectories were retrieved by latent class growth analysis (LCGA). Multinomial logistic regression was used to calculate risk ratios. Results: 545 participants were included. Four distinct pain trajectories were uncovered by LCGA. We found significant differences in baseline characteristics, including body mass index (BMI); symptom severity; pain coping strategies and in criteria for clinical hip OA (American College of Rheumatology (ACR)). Lower education, higher activity limitation scores, frequent use of pain transformation as coping strategy and painful internal hip rotation were more often associated with trajectories characterized by more severe pain. No association was found for baseline radiographic features. Conclusion: We defined four distinct pain trajectories over 5 years follow-up in individuals with early symptomatic hip OA, suggesting there are differences in symptomatic progression of hip OA. Baseline radiographic severity was not associated with the pain trajectories. Future research should be aimed at measuring symptomatic progression of hip OA with even more frequent symptom assessment.